2010
DOI: 10.1016/j.juro.2010.03.078
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality and Psychosocial Functioning in Young Women After Colovaginoplasty

Abstract: Based on the scoring system outcome colovaginoplasty seems to be an excellent choice to manage vaginal agenesis and ensure good quality of general and sexual life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 28 publications
2
26
1
2
Order By: Relevance
“…Hysteroscopic metroplasty for uterine septae has been shown to significantly improve reproductive performance in women undergoing assisted reproduction as well as those with previous recurrent pregnancy loss. 39,40,51,55,56 Caring for women with vaginal agenesis and other uterine and vaginal anomalies should be done in centers with interdisciplinary expertise in attending to all the psychological, surgical and medical expertise.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hysteroscopic metroplasty for uterine septae has been shown to significantly improve reproductive performance in women undergoing assisted reproduction as well as those with previous recurrent pregnancy loss. 39,40,51,55,56 Caring for women with vaginal agenesis and other uterine and vaginal anomalies should be done in centers with interdisciplinary expertise in attending to all the psychological, surgical and medical expertise.…”
Section: Resultsmentioning
confidence: 99%
“…40 The intestinal vaginoplasty can provide a reliable option for those patients who have been unable to dilate and maintain a neovagina created by other methods. Sigmoid colon can readily be mobilized on a vascular pedicle and transposed into the pelvis as a neovagina and is most commonly used.…”
Section: Intestinal Vaginoplastymentioning
confidence: 99%
See 1 more Smart Citation
“…The short-term cosmetic outcome was very good. In patients with MRKH syndrome and normal anus, several follow-up studies have shown that colovaginoplasty is an acceptable option for replacement of the vagina [21,22]. Hensle et al [21] showed that 78% of 36 patients who were evaluated reported sexual satisfaction after bowel vaginoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…After gonadal dysgenesis, MRKH is the second most common cause of primary amenorrhea [2]. Nonsurgical vaginal dilation or surgical creation of a neovagina are among the treatment options, and allow for normal sexual intercourse [3,4].…”
Section: Introductionmentioning
confidence: 99%